The Cardiovascular Burden of Fine Particulate Matter in Asia: A Systematic Review and Meta-Analysis of Hypertension Risk - Hafizah Latif; Wahyudi (HM Publisher, 2026)
Background: The epidemiological transition in Asia has precipitated a double burden of disease, where rapid industrialization intersects with an aging demographic to drive a surge in cardiovascular mortality. Hypertension remains the predominant modifiable risk factor in this context. While the correlation between fine particulate matter (PM2.5) and elevated blood pressure is documented in Western literature, evidence regarding Asian populations remains fragmented. This region faces a unique toxicological phenotype characterized by extreme exposure concentrations, distinct particulate composition including biomass and dust, and specific genetic susceptibilities, necessitating a dedicated regional analysis. Methods: We conducted a systematic review and meta-analysis of observational studies published between 2017 and 2024, searching PubMed, Scopus, and Embase. We critically appraised exposure assessment methods, distinguishing between satellite-based estimates and ground monitoring, and performed a quality audit using the Newcastle-Ottawa Scale. To minimize temporal bias, we stratified analyses by study design into Incident Hypertension (Cohort studies) and Prevalent Hypertension (Cross-sectional studies). Results: Nine pivotal studies encompassing over 600,000 participants from China, Taiwan, India, South Korea, and Thailand were synthesized. The random-effects meta-analysis revealed a significant pooled Hazard Ratio of 1.12 (95% CI 1.06 to 1.18) per 10 micrograms per cubic meter increase in long-term PM2.5. Heterogeneity was significant (I2 equals 90.2%), driven by regional variations. High-altitude cohorts in Tibet and high-exposure regions in India demonstrated synergistic risks with Odds Ratios exceeding 1.50 compared to moderate-exposure regions in Taiwan. Conclusion: Long-term PM2.5 exposure is a potent, independent driver of hypertension in Asia. The data suggest a synergistic interaction between hypoxia and pollution, and a non-linear dose-response curve at high concentrations. Clinicians should consider residence in high-pollution zones a cardiovascular risk enhancer equivalent to traditional risk factors.